2007
DOI: 10.1016/j.bbrc.2007.05.077
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence resonance energy transfer analysis of subunit assembly of the ASIC channel

Abstract: Acid-sensing ion channels (ASICs) are believed to be homo-or heteromeric complexes, which have been verified by classical methods such as co-immunoprecipitation or electrophysiological assays. However, the exact subunit combinations of ASICs in living cells have not been established yet. Here, we apply assays based on fluorescence resonance energy transfer (FRET) between GFP color mutants CFP and YFP to investigate ASIC assembly directly in living cells. Homomerization as well as heteromerization of different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…Fluorescence resonance energy transfer analysis suggested that the ASIC1a/2a heteromer contains at least two ASIC1a and two ASIC2a subunits (17). In agreement, several studies reported that the related epithelial Na + channel (ENaC) is composed of four (18)(19)(20)(21) or nine subunits (22)(23)(24).…”
mentioning
confidence: 56%
“…Fluorescence resonance energy transfer analysis suggested that the ASIC1a/2a heteromer contains at least two ASIC1a and two ASIC2a subunits (17). In agreement, several studies reported that the related epithelial Na + channel (ENaC) is composed of four (18)(19)(20)(21) or nine subunits (22)(23)(24).…”
mentioning
confidence: 56%
“…in which D and A are molar extinction coefficients for the donor and acceptor, respectively, at the donor excitation wavelength (Takanishi et al, 2006;Gao et al, 2007). For the control groups, Kv2.1⌬C1a-Yϩ C-syx and Kv2.1⌬331-Yϩ C-syx, data presented were extracted from eCFP/eYFP molar ratio Ͼ3 at which saturation of FRET occurred.…”
Section: Fret Analysis and Confocal Microscopymentioning
confidence: 99%
“…ASIC1a, ASIC2a, and ASIC2b are expressed throughout the brain with particularly high abundance in the cerebral cortex, hippocampus, amygdala, olfactory bulb, and the cerebellum (GarciaAnoveros et al 1997;Lingueglia et al 1997;Price et al 1996;Waldmann et al 1996Waldmann et al , 1997. ASIC1a forms not only heteromeric channels with ASIC2a, but also Ca 2ϩ -permeable homomeric channels Bassilana et al 1997;Benson et al 2002;Gao et al 2007;Hesselager et al 2004;Yermolaieva et al 2004). ASIC1a is enriched in synaptosomal fractions and expressed in dendritic spines Wemmie et al 2002).…”
Section: Introductionmentioning
confidence: 99%